2023
DOI: 10.1002/chem.202381662
|View full text |Cite
|
Sign up to set email alerts
|

Frontispiece: Detection of the Dark States in Thermally Activated Delayed Fluorescence (TADF) Process of Electron Donor‐Acceptor Dyads: Insights from Optical Transient Absorption Spectroscopy

Abstract: Unraveling the complicated photophysics of thermally activated delayed fluorescence (TADF) compounds is not a trivial task, although it is critical to improve the performance of TADF emitters in OLED. In the Review by Zhao and colleagues (DOI: 10.1002/chem.202203737), recent developments of using the transient optical spectroscopic methods to study the photophysics of TADF emitters are summarized, e. g. the manifestation of the theoretically proposed spin‐vibronic coupling effect and the three‐state model desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…These results show that a subtle variation of the molecular structure, even the linker, may impose a significant effect on the photophysical properties of electron donor–acceptor dyads. This is also solid experimental evidence that having 1 CS, 3 CS, and 3 LE states sharing similar energy is essential for TADF since the 3 CS → 1 CS process is too slow to produce any TADF . Moreover, it should be noted that the prompt fluorescence lifetime of PTZ-Ph-AQ , 62 ns, is exceptionally long for electron donor–acceptor type TADF emitters. ,, Note that the E T1 of the 2-phenylanthraquinone is 2.33 eV, and for the native AQ, the T 1 state energy is ca.…”
Section: Resultsmentioning
confidence: 53%
See 2 more Smart Citations
“…These results show that a subtle variation of the molecular structure, even the linker, may impose a significant effect on the photophysical properties of electron donor–acceptor dyads. This is also solid experimental evidence that having 1 CS, 3 CS, and 3 LE states sharing similar energy is essential for TADF since the 3 CS → 1 CS process is too slow to produce any TADF . Moreover, it should be noted that the prompt fluorescence lifetime of PTZ-Ph-AQ , 62 ns, is exceptionally long for electron donor–acceptor type TADF emitters. ,, Note that the E T1 of the 2-phenylanthraquinone is 2.33 eV, and for the native AQ, the T 1 state energy is ca.…”
Section: Resultsmentioning
confidence: 53%
“…Under ideal circumstances, the molecular orbital occupancy is literally the same for both 1 CS and 3 CS states, with the radical anion localized on the acceptor and radical cation confined on the donor. The electronic absorption of the 1 CS state, i.e., the sum of the absorption bands of the D 0 + → D n + transition confined on the donor (radical cation) and the A 0 – → A n – transition confined on the acceptor (radical anion) are the same as compared to the electronic absorption of the 3 CS state, making it difficult to discriminate between these two states by transient optical absorption spectroscopic methods. , Although our recent study shows that this is not always the case, clearly more examples are needed to elucidate this issue.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…In the previously reported dyad, an alkylamine was attached to the imide N-atom. 32 It was shown that the redox potentials of the aromatic imide can be tuned by attaching electron-withdrawing moieties to the imide N-atom, 57 and thus we used aniline-containing electron-donating and electron-withdrawing moieties to prepare dyads (Scheme 1). We expected to tune the CT state energy, and thus the TADF property of the dyads, given that it is known that the TADF property of compact orthogonal dyads is strongly dependent on the energy of their 1 CT, 3 CT and 3 LE states (in terms of the energy gap and energy ordering).…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, SOCT-ISC is another fundamental principle employed for the development of functional materials, such as thermally activated delayed fluorescence (TADF). 27–32 Electron donor–acceptor dyad-based TADF emitters have attracted significant attention, because this type of compounds can be used as third-generation emitters in organic light-emitting diodes (OLEDs) to harvest both the singlet and the triplet excitons produced by CR in the light-emitting layer. 33–38 To date, although many electron donor–acceptor dyads have been developed as TADF emitters for the fabrication of OLED devices, the detailed photophysics of TADF emitters are still not fully understood.…”
Section: Introductionmentioning
confidence: 99%